ギョガン レンズ カメラ 2テン カンソク ニ ヨル ナンキョク ショウワキチ ノ カキ ノ ウンコウ ニツイテ - 菊地, 勝弘; キクチ, カツヒロ; 福谷, 博; フクタニ, ヒロシ; 笠原, 喜美子; カサハラ, キミコ; KIKUCHI, Katsuhiro; FUKUTANI, Hiroshi; KASAHARA, Kimiko (国立極地研究所, 1976)
P(論文) 第9次日本南極地域観測隊のメンバーとして,昭和基地での越冬観測中の1968年11,12の両月,昭和基地北方および東方の海氷上に2ヵ所の観測点を設け,魚眼レンズカメラによるこの周辺の夏季の雲高および雲向・雲速の観測を行った.魚眼レンズによる画像周辺部や天頂付近のケースを除けば,10%程度の誤差で雲高が求められ,その結果,上層雲(絹雲,絹積雲,絹層雲)は5-8km,中層雲のうち高積雲は2-3km,下層雲の層積雲は1km前後の高度で出現していることがわかった.計算された高度は,ラジオゾンデから期待される高度とはいずれの雲についてもほぼ妥当であったが,目視観測との比較では中層雲,下層雲はよく一致していたが,上層雲に関しては,目視で報告される4-5kmよりは高かった.雲向はその高度の風向とほぼ平行であり,雲速もまた,その高度の風速と一致しているケースが多かった.これらのことから目視による上層雲の高度は,少し低目であると結論された. Cloud height, direction and velocity were measured by means of stereoscopic observation using two fish-eye lens cameras in the summer season of 1968 at Syowa Station, Antarctica. Although the method is somewhat uncertain in regard of observational and analytical errors, we can obtain the cloud height within a range of error of 10 percent if the location of the clouds for observation, is carefully selected, with the exception of the periphery and around the zenith of images of fish-eye lens photographs. The results of the analysis were as follows : In the case of Ci, Cc and Cs of high level clouds, the height was within a range of 5 to 8km in the case of Ac cloud at the middle level the height was within a range of 2 to 3km and in the Sc cloud at the low level the height was approximately 1km. These heights coincided in all cases with the cloud heights estimated from the sounding curves obtained by routine radiosonde observation. On the other hand, in comparison with the heights reported by routine naked eye observation, they coincided with the cases of Ac and Sc clouds alone, whereas, in the case of the high level clouds, the cloud heights were different from each other. The reported heights of the high level cloud by naked eye observation were in a range of 4 to 5km invariably. The calculated direction and velocity of each cloud based on the data observed by fish-eye lens cameras coincided closely with the direction and velocity at the same level estimated by the radiosonde observations. From these results the calculated cloud heights at all levels are considered reasonable, and it is ...